Impact of the anti-vaccine movement on brazilian public health - Garcia, Bruna Maria de Campos; Penacci, Fernanda Augusta (JRG Journal of Academic Studies, 2024)
Objective: To analyze the impact of the anti-vaccine movement on Brazilian public health and its relationship with the return of vaccine-preventable diseases and the reduction in vaccination coverage in Brazil. Methodology: This is an integrative review of the literature that was carried out in accordance with the recommendation of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline, the search was carried out in the LILACS and SCIELO databases and conducted by the PICO strategy. Results: For the corpus of analysis, 17 articles published in the period from 2019 to 2024 were included, namely: 1 ecological study, 3 mixed studies, 1 epidemiological study, 2 qualitative ones of an exploratory nature, 2 scoping reviews, 3 cross-sectional studies, 4 literature reviews and 1 semantic cross-cultural adaptation. Conclusion: The anti-vaccine movement directly impacts Brazilian public health and it is necessary that health professionals are always qualified and trained on vaccines in order to disseminate scientifically proven information to encourage and encourage individuals to get vaccinated. Furthermore, strategies are needed to mitigate vaccine hesitancy in the country, such as: formulation of public policies, organization of services and health units and formulation of algorithms through social networks with the aim of detecting false content and penalizing people who disseminate it.